Fistula-in-ano conversion combined with cutting seton for simple transsphincteric fistula-in-ano - Chen Fujun; Liu Changping; Li Shan; Cheng Yingjie; Zan Chaoyuan; Li Gang; Li Chengshu; Luo Chuanyun; He Ping (结直肠肛门外科)
[Objectives] To investigate the clinical effectiveness of fistula-in-ano conversion combined with cutting seton for simple transsphincteric fistula-in-ano. [Methods] This was a retrospective analysis of 60 patients with simple transsphincteric fistula-in-ano treated at the First People’s Hospital of Longquanyi District, Chengdu between January and October 2020. Patients were divided into the treatment group (n=30, receiving fistula-in-ano conversion combined with cutting seton) and the control group (n=30, receiving incision, seton, and drainage). The following data were compared between the two groups: effectiveness, operation time, postoperative hospitalization, time to wound healing, pain at 24 hours postoperative using the Numeric Rating Score, and anal function at 3 months postoperative using the Wexner anal incontinence score. [Results] The two groups were comparable concerning overall effectiveness, the cured rate, and the overall markedly effective rate (P>0.05). The operation time was significantly longer in the treatment group, while the time to wound healing was significantly shorter in the treatment group (P<0.05). Postoperative hospitalization was similar between the two groups (P>0.05). Pain score of the Numeric Rating Scale at 24 hours postoperative and the Wexner anal incontinence score at 3 months postoperative was significantly lower in the treatment group than in the control group (P<0.05). [Conclusion] Fistula-in-ano conversion combined with cutting seton is an effective procedure for simple transsphincteric fistula-in-ano. Compared with incision, seton, and drainage, it can shorten the time to wound healing, alleviate postoperative pain, and has less impact on anal function.